Identification of Coastal Waste in Pariaman City - Rahmi, Lailatur; Angraina, Dilla; Fitriah, Rahmuliani (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
Marine Debris is a collection of solid materials left behind that intentionally or unintentionally in the sea that have an impact on threatening the sustainability and sustainability of marine ecosystems. This research is a study of identifying marine waste that is on the coast of Kota Pariaman. This study aims to identify marine waste by type and size. The collection of marine waste is carried out in a transect that is stretched to follow the coastline at the lowest tide with a distance of 100 m divided by 20 m each, each 20m each 5m x 5m each (5 meters towards the sea, 5 meters landward). Classification of waste using an LCS or litter classification system. LCS is a marine waste type coding system. This system is used for sampling carried out in its original place and immediately measures the weight and amount of waste. The method used to determine the transect is by utilizing the Geographic Information System (GIS) technology using a quantitative approach. The GIS technology can to geographically collect, manage, manipulate and visualize spatial (spatial) data related to the position of the earth's surface on the map according to the actual position of the earth's surface with coordinates. The results showed that in the coastal city of Pariaman dominated by the basket flakes with 2.67 gr (garbage Meso) or 1.52 types of garbage/m2 and 77.01 gr of beverage bottles (macro) or 0.80 type of garbage/m2.